Comparison of Clinicopathologic and Oncological Outcomes Between Transurethral En Bloc Resection and Conventional Transurethral Resection of Bladder Tumor: A Systematic Review, Meta-Analysis, and Network Meta-Analysis with Focus on Different Energy Sources - Sari Motlagh, Reza; Rajwa, Pawel; Mori, Keiichiro; Laukhtina, Ekaterina; Aydh, Abdulmajeed; Katayama, Satoshi; Yanagisawa, Takafumi; König, Frederik; Grossmann, Nico C; Pradere, Benjamin; Mostafai, Hadi; Quhal, Fahad; et al. (Journal of endourology, 2022)
Introduction: It has been hypothesized that transurethral en bloc (TUEB) of bladder tumor offers benefits over conventional transurethral resection of bladder tumor (cTURBT). This study aimed to compare disease outcomes of TUEB and cTURBT with focus on the different energy sources. Methods: A systematic search was performed using PubMed and Web of Science databases in June 2021. Studies that compared the pathological (detrusor muscle presence), oncological (recurrence rates) efficacy, and safety (serious adverse events [SAEs]) of TUEB and cTURBT were included. Random- and fixed-effects meta-analytic models and Bayesian approach in the network meta-analysis was used. Results: Seven randomized clinical trials (RCTs) and seven non-RCTs (NRCT), with a total of 2092 patients. The pooled 3- and 12-month recurrence risk ratios (RR) of five and four NRCTs were 0.46 (95% CI 0.29-0.73) and 0.56 (95% CI 0.33-0.96), respectively. The pooled 3- and 12-month recurrence RRs of four and seven RCTs were 0.57 (95% CI 0.25-1.27) and 0.89 (95% CI 0.69-1.15), respectively. The pooled RR for SAEs such as prolonged hematuria and bladder perforation of seven RCTs was 0.16 (95% CI 0.06-0.41) in benefit of TUEB. Seven RCTs (n = 1077) met our eligibility criteria for network meta-analysis. There was no difference in 12-month recurrence rates between hybridknife, laser, and bipolar TUEB compared with cTURBT. Contrary, laser TUEB was significantly associated with lower SAEs compared with cTURBT. Surface under the cumulative ranking curve ranking analyses showed with high certainty that laser TUEB was the best treatment option to access all endpoints. Conclusion: While NRCTs suggested a recurrence-free benefit to TUEB compared with cTURBT, RCTs failed to confirm this. Conversely, SAEs were consistently and clinically significantly better for TUEB. Network meta-analyses suggested laser TUEB has the best performance compared with other energy sources. These early findings need to be confirmed and expanded upon.
Keywords: TURBT; Female; TUEB; urologické chirurgické výkony; en bloc; Humans; cystektomie; ženské pohlaví; mužské pohlaví; Cystectomy; nádory močového měchýře; lidé; Male; Urinary Bladder Neoplasms; bladder cancer; transurethral en bloc; Urologic Surgical Procedures; transurethral resection